CO2 FLUX IN INDONESIAN WATER DETERMINED BY SATELLITE DATA - Ni Wayan Ekayanti; Abd. Rahman as-syakur (BRIN, 2011)
The oceans was considered to be a major sink for CO2. The improving of quantitative and qualitative description about the ability of sea in uptaking or emitting CO2 is a great scientific concern in meteorological and climatological science. Measurement of the ability of sea in uptake or emitting CO2 could determined by measuring the CO2 exchange coefficient on sea interface and the measuring the different partial pressure of CO2 between the air and sea. In this study, CO2 flux distribution of Indonesian waters in 2007 to 2009 was computed using monthly CO2 exchange and the different partial pressure of CO2 estimated from wind speed, salinity, SST, and sea characteristic, which were obtained from satellite data. The carbon dioxide flux thus was estimated and discussed by two different designs of transfer velocity (k), of Wanninkhof (1992), kW92 relationship and by Nightingale et al. (2000), kN, relationship. The result indicated that generally, Indonesian water was emitting the CO2 to the air. Average CO2 emitting from sea to the air for recent year in 2007 to 2009 are 3.80 (mol m-2year-1) and 2.85 (mol m-2year-1) with kW92 relationship and kN relationship calculation, respectively. The total average CO2 emission from sea to the air in 2007 to 2009 for the Indonesian waters areas are 0.15 (PgC year-1) and 0.12 (PgC year-1) based on kW92 relationship and kN relationship calculations, respectively.